Sumbangan Ibn Khaldun Dalam Pemikiran Ekonomi Islam dan Relevensinya dengan Permasalahan Ekonomi Semasa - Borhan, Joni Tamkin (Afkar: Jurnal Akidah dan Pemikiran Islam, 2000)
This article discusses critically the contribution of Ibn Khaldun, one of the strongest personalities of Arabo-Muslim culture, to Islamic economic thoughts and its relevance to the contemporary problems of modern economics. The topics that will be discussed include a short biography of Ibn Khaldun, economic philosophy, theories of production, division of labour and exchange, theory of market system and market regulation, theories of value, money and prices, theory of distribution, public finance, theory of growth and business cycles, theory of macro economics and the role of government in economic activity, and theory of international trade.